2013
DOI: 10.1038/bjc.2013.455
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PTEN expression is an independent predictor of favourable survival in endometrial carcinomas

Abstract: Background:We and others previously reported the prognostic significance of PTEN mutational status on favourable survival in endometrial carcinomas. Here, we demonstrate that loss of PTEN expression in immunohistochemistry is an independent prognostic marker for favourable survival in endometrial carcinomas.Methods:We conducted immunohistochemical analyses of PTEN, PIK3CA, phosphorylated Akt (p-Akt), and p27 in primary endometrial carcinomas from 221 patients. Mutation of PTEN was analysed further.Results:Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 12 publications
2
31
1
1
Order By: Relevance
“…With regards to PTEN status in EEC, several studies report that there is an association with PTEN status and progression in EEC but even here there are discrepancies. Some studies state that a PTEN-positive status is associated with a favourable prognosis (Kanamori et al 2002, Uegaki et al 2005 and that with higher stages of EEC, PTEN loss increases (Daniilidou et al 2013), but two studies suggest that a PTEN-negative status is associated with a favourable prognosis (Mackay et al 2010, Akiyama-Abe et al 2013. The present study found no association between PTEN status and progression-free survival in EEC or any difference between PTEN status and FIGO stage.…”
Section: Discussioncontrasting
confidence: 54%
“…With regards to PTEN status in EEC, several studies report that there is an association with PTEN status and progression in EEC but even here there are discrepancies. Some studies state that a PTEN-positive status is associated with a favourable prognosis (Kanamori et al 2002, Uegaki et al 2005 and that with higher stages of EEC, PTEN loss increases (Daniilidou et al 2013), but two studies suggest that a PTEN-negative status is associated with a favourable prognosis (Mackay et al 2010, Akiyama-Abe et al 2013. The present study found no association between PTEN status and progression-free survival in EEC or any difference between PTEN status and FIGO stage.…”
Section: Discussioncontrasting
confidence: 54%
“…Mutations in the PTEN gene, a tumor suppressor and a negative regulator of PI3K activation, are thought to be one of the earliest events in Type I EC tumorigenesis, while PIK3CA mutations occur late and are thought to be associated with invasion . PTEN immunohistochemistry has the ability to capture functional PTEN loss in addition to genomic PTEN loss, and has been shown to be an independent predictor of favorable survival in endometrial cancer . Mutations in AKT, the primary effector of PI3K activity, are thus far rarely reported in endometrial cancer .…”
Section: Resultsmentioning
confidence: 99%
“…20 PTEN immunohistochemistry has the ability to capture functional PTEN loss in addition to genomic PTEN loss, 21 and has been shown to be an independent predictor of favorable survival in endometrial cancer. 22,23 Mutations in AKT, the primary effector of PI3K activity, are thus far rarely reported in endometrial cancer. 24 Figure 2b shows that the PI3K/ PTEN/AKT pathway is most frequently dysregulated within Type I and mucinous histology, with PIK3CA mutated in 36% of Type I and 33% mucinous; PTEN mutated in 41% Type I and 50% mucinous; PTEN loss in 70% of Type I and mucinous EC; and AKT mutation in 5% of EC and 6% of mucinous samples.…”
Section: Genomic and Molecular Characterizationmentioning
confidence: 99%
“…PTEN gene mutations are seen in 18-55% of endometrial precancers, 26-80% of endometrioid adenocarcinomas [16]. Akiyama-Abe et al reported that expression of PTEN was lost in 56 endometrial carcinoma patients (25%) [17]. Heejeong et al showed that PTEN loss was significantly higher in endometrial carcinoma compared with simple hyperplasia (68% vs. 24%), and it was also higher in complex atypical hyperplasia compared with simple hyperplasia (71% vs. 24%) [18].…”
Section: Discussionmentioning
confidence: 99%